Concise oxford english dictionary; south asia edition (Oxford Oxford University Press, 2011)
The twelfth edition of this world-famous bestseller gives the most up-to-date picture of the English language today. The original 1911 edition, revolutionary at the time for its focus on current English and its use of illustrative examples, combined a succinct yet approachable style with coverage of everyday as well as specialist terms
Keywords: Dictionary; English Dictionary-South Asia Ed.; Reference book